Neuroendocrine–Immune Systems Response to Environmental Stressors in the Cephalopod Octopus vulgaris - Di Cosmo, Anna; Polese, Gianluca (Frontiers in Physiology, 2016)
Under a continuous changing environment, animals are challenged with stresses and stimuli which demanding adaptation at behavioral and physiological levels. The adaptation strategies are finely regulated by animal nervous, endocrine and immune systems. Although it’s been established by now the usage of integrative approach to the study the endocrine and nervous systems (neuroendocrine), yet our understanding of how they cooperate with the immune system remains far from complete. The possible role that immune system plays as a component of the network has only been recognized recently. Octopus vulgaris is an important member of cephalopods and is considered as a model species, with considerable information about the neuroendocrine and immune systems. In the current review, we anticipate to shed light on the complexity and cross talk among the three systems and how they cooperate in setting physiological response to stresses-stimuli in Octopus vulgaris as a target species and primary example.